Crucifixion of the Identity: Persons and Beings, Bodies and Genes - Jurić, Hrvoje, filozof (Array, 2010)
Regarding the recent advances in the field of science and technology – primarily within information and communication technology, and biotechnology – human as an individual and humankind altogether are facing challenges of a new kind, while the questions on personal and human identity are becoming more complex than ever. Old questions about identity, e. g. "Who am I?", "Who are we?", "Who (or what) is human?" have to be asked in some new contexts. Possible answers to these questions have significant specific weight in epistemological, ontological and anthropological perspective, but they also have to include ethical and socio-political aspects. We must not be infatuated by the emancipatory potential of modern technoscience to the extent that we stop to question new types of manipulation or even enslavement of the human and the humankind. Moreover, we must not stop at the boundaries of the human – we must extend the traditional ethical questions over into the field of bioethics or transhumanist ethics (cyborg ethics, animal ethics, ecoethics, cosmoethics). However, the epistemic barycentre is still in the sphere of the human. Therefore we need to investigate where the human is and what is a human on the crucifix of the identity whose endpoints represent: being a (distinctive) person and being a (human) being, (visible) embodiment and (invisible) genetic constitution. Qualitative and numerical identity, personal and human identity, identity of organism and genetic identity have to be examined in terms of definition and protection, i.e. description and normativity. In this manner, as theoreticians, we are facing the imperative of proper focusing which helps us to articulate and understand the problem, and on the other hand, as persons and members of the humankind, we are facing the impossibility of disentangling the knot of the identity and the identity tension, exactly like in the 1973 installation (video-sculpture) "Crucifixion of the Identity" by Peter Weibel, which will serve as an illustration of this subject field.